2003
DOI: 10.1088/0953-8984/15/10/313
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of three-parameter equation of state of solids: compatibility with first principles approaches and application to solids

Abstract: In a recent paper we have proposed a three-parameter equation of state (EOS) of solids, and applied it to a few isotherms and shown that the fits are uniformly excellent. In this paper a comprehensive comparison of the applicability of our model is made with seven existing three-parameter EOSs. We have applied our model along with seven existing three-parameter EOSs, with no constraint on the parameters, to accurate and model-independent isotherms of nine solids and studied the fitting accuracy and agreement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 49 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…It is found that some other inverted type EOS due to earlier workers [57] can also be derived from a generalized version.…”
Section: Behaviour In the Limit Of Infinite Pressurementioning
confidence: 73%
“…It is found that some other inverted type EOS due to earlier workers [57] can also be derived from a generalized version.…”
Section: Behaviour In the Limit Of Infinite Pressurementioning
confidence: 73%
“…[31][32][33][34] The other approach is to find a mathematical function which gives the best fit to the experiments. [35][36][37][38] Roy and Roy 39 gave a good review and evaluate the fittings of the currently used EOSs. Their proposed 40 threeparameter empirical EOS is…”
Section: Empirical Eossmentioning
confidence: 99%
“…One uses the original Eulerian strain or Interatomic potential EoSs and refines their parameters in order to find a better fit to experiments [31][32][33][34] . The other approach is to find a mathematical function which gives the best fit to the experiments [35][36][37][38] .…”
Section: Empirical Eossmentioning
confidence: 99%
“…Thus there will be a perfect synchronization between the two approaches. However, we do not have, at the moment, an unambiguous set of bulk modulus data even for a solid as simple as NaCl [37] and as stable as Cu, as discussed later. Furthermore, the experimental uncertainty, accompanying the measured bulk modulus values, in general, is much larger than those for the measured isotherms.…”
Section: Introductionmentioning
confidence: 95%
“…An obsession of various workers with the appropriateness of the 'input' approach [17,45,46,50,70,80], over the decades, in conjunction with the paucity of the experimentally measured values of B 0 , has, in fact denied the three-parameter EOSs as much attention as the two-parameter EOSs, in respect of their utility. However, the traditionally accepted view that the inclusion of increasing number of parameters would increasingly improve the behaviour of an EOS towards experiments is not necessarily true, for reasons referred to in [37]. Sometimes the authors, viz [47], obsessed with the 'input' approach, but confronted with the problem of selection of data, picked up a measured value of B 0 of their choice, and treated B 0 as a fitting parameter to achieve the best fit to the higher-pressure EOS curves.…”
Section: Introductionmentioning
confidence: 99%